System security model based on trusted access control under cloud computing environment. (2017) - Wang, Fengqi
It has become a hot spot of cloud security to provide good service for legal user, and prevent access from illegal user or illegal access from legal user. Therefore, it is urgent to design a reasonable access control security model under cloud computing. This paper discusses trust definition and computation in cloud computing environment and uses scientific methods to compute comprehensive trust degree. Then based on RBAC model the conception of trust is introduced to form a trust-based access control model. The security model satisfies the design for access control mechanism in opened system, by establishing indirect user-role distribution relation and context constrain which reflecting context information. The formal definition and access control policies of the model are explained. The scheme can dynamically determine the authorisation according to the user's trust value, so it can detect the user's abnormal behaviour at any time and respond in a timely manner. The simulations shows this model can effectively help users in cloud service to make choices on security and reliability, and it also shows better dynamic property to prevent abnormal behaviours of the users.